PERILAKU MASYARAKAT PEMBELI SEPEDA MOTOR HONDA SECARA KREDIT DI PT. DAYA ADIRA WISESA MANADO - Kainde, Geiby Gertrudis (HOLISTIK, Journal Of Social and Culture, 2013)
The high rates sales of Honda motorcycles brands today, shows the demand of motor vehicles, especially two-wheeler that can be assumed to be no longer a secondary requirement but began to turn into a primary requirement. Seeing these conditions cause more businesses are required to have appropriate strategies to meet the target sales volume. Given the increasingly dynamic development of technology, people are required to quickly and precisely to act so as not to compete. Size of the potential market for motorcycles led to increasing competition. Through increased productivity, innovation and marketing as well as network management supported continuous improvement efforts in a variety of business processes, information technology and human resource quality, PT. Daya Adicipta Wisesa will overcome these challenges. The success of the marketing activities of a company is determined by the ability of the company to explore the perceptions of buyers or consumers, so as to know why someone would prefer to buy a product and brand Honda is not other brands. Perception that pose a buyer preference towards a particular brand of a product called the behavior of the buyer or consumer behavior. The emergence of the company's relationship with the community dynamics of consumers is basically a phenomenon can be seen from the rise of consumer communities that have sprung up and are then responded to by the company with a wide range of marketing activities to retain the presence of the consumer community that has been formed. Keywords: motorcycle, consumers, community